Large-scale fabrication of ion-selective electrodes for simultaneous detection of Na+, K+, and Ca2+ in biofluids using a smartphone-based potentiometric sensing platform - Teekayupak, Kanyapat; Lomae, Atchara; Agir, Ismail; Chuaypen, Natthaya; Dissayabutra, Thasinas; Henry, Charles S.; Chailapakul, Orawon; Ozer, Tugba; Ruecha, Nipapan (Mikrochimica acta (1966), 2023)
A significant bottleneck exists for mass-production of ion-selective electrodes despite recent developments in manufacturing technologies. Here, we present a fully-automated system for large-scale production of ISEs. Three materials, including polyvinyl chloride, polyethylene terephthalate and polyimide, were used as substrates for fabricating ion-selective electrodes (ISEs) using stencil printing, screen-printing and laser engraving, respectively. We compared sensitivities of the ISEs to determine the best material for the fabrication process of the ISEs. The electrode surfaces were modified with various carbon nanomaterials including multi-walled carbon nanotubes, graphene, carbon black, and their mixed suspensions as the intermediate layer to enhance sensitivities of the electrodes. An automated 3D-printed robot was used for the drop-cast procedure during ISE fabrication to eliminate manual steps. The sensor array was optimized, and the detection limits were 10 –5 M, 10 –5 M and 10 –4 M for detection of K + , Na + and Ca 2+ ions, respectively. The sensor array integrated with a portable wireless potentiometer was used to detect K + , Na + and Ca 2+ in real urine and simulated sweat samples and results obtained were in agreement with ICP-OES with good recoveries. The developed sensing platform offers low-cost detection of electrolytes for point-of-care applications. Graphical abstract